The Narcissus Myth in Early Renaissance French Literature: Fragment, Allegory, Emblem - Irina K. Staf (Studia Litterarum)
This article examines the evolution of medieval interpretations of the myth of Narcissus (Ovid, The Metamorphoses, Book III) in French literature of the first half of the 16th century. Jeanne Flore in the “Comptes amoureux” develops the courtesan interpretation of the myth, in which Narcissus, who rejects Cupid’s omnipotence, is combined with the figure of Belle dame sans mercy. In the tradition of moral and allegorical commentary, the young man in love with himself served as a symbol of hubris excessively immersed in worldly goods; in the mid-century, this tradition changed under the influence of humanism: with François Habert and Barthélémy Aneau the story of Narcissus illustrates the maxim “know thyself.” Reception of the Metamorphoses in the Middle Ages implied a fragmentation of the text of the poem: the courtly interpretation referred to its separate subjects, while the allegorical interpretation transformed it into a list of symbolic characters with a stable independent meaning and into a set of didactic maxims of a universal character. During the Renaissance, literati seek to restore the coherence of Ovid’s text. This tendency is embodied not only in new translations (by Clément Marot, F. Habert, B. Aneau) but also, paradoxically, within the genre of the emblem. The “Metamorphose d’Ovide figurée” inherits the medieval florilegiums and transforms the tradition of illuminated manuscripts: on the one hand, it replaces the text of the poem with a series of engravings, while, on the other, its emblems arrangement recreates the unity of the poem. Ovid’s emblematic treatment embodies Horace’s principle of ut pictura poesis.